2005
DOI: 10.1097/01.mbc.0000188411.94740.d7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying hypocoagulable states with a modified global assay of overall haemostasis potential in plasma

Abstract: To test the sensitivity of the global assay of overall haemostasis potential (OHP) in detecting hypocoagulation, the OHP was assayed in plasma containing exogenous thrombin (0.04 IU/ml), tissue-plasminogen activator (330 ng/ml), Ca and a platelet reagent. Commercial plasmas with factor II, V, VIII, IX, X, XI, XII or VII deficiency were mixed with normal plasma in different proportions to imitate different severities. Samples from patients with haemophilia and factor XII deficiency were also examined. No clot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
5
17
0
Order By: Relevance
“…The OHP has demonstrated sensitivity to changes in both coagulation and fibrinolytic factors. In vitro experiments using factor deficient plasma have demonstrated significant correlations between OHP parameters and concentrations of factors II, V, VII, VIII, IX and X and XI [142]. These results were replicated in our laboratory, and we also have shown using in-vitro experiments that the OFP parameter is sensitive to varying concentrations of plasminogen, α2-plasmin inhibitor, PAI-1, TAFI and the fibrinolytic inhibitor tranexamic acid [unpublished data and 143].…”
Section: Overall Haemostatic Potential (Ohp)supporting
confidence: 61%
“…The OHP has demonstrated sensitivity to changes in both coagulation and fibrinolytic factors. In vitro experiments using factor deficient plasma have demonstrated significant correlations between OHP parameters and concentrations of factors II, V, VII, VIII, IX and X and XI [142]. These results were replicated in our laboratory, and we also have shown using in-vitro experiments that the OFP parameter is sensitive to varying concentrations of plasminogen, α2-plasmin inhibitor, PAI-1, TAFI and the fibrinolytic inhibitor tranexamic acid [unpublished data and 143].…”
Section: Overall Haemostatic Potential (Ohp)supporting
confidence: 61%
“…Thus highly significant correlations between OHP levels and rising concentrations of different coagulation factors (II, V, VII, VIII, IX, X, and XI) were observed in an in vitro model. 13 Furthermore, investigation of plasma from patients with different severities of hemophilia A indicated that OHP levels correlated better with clinical features in these patients than those that could be concluded from the actual levels of FVIII or aPTT. This is in accordance with findings in clinical practice that patients having similar levels of deficiency of clotting factors show different degrees of severity in clinical presentation and bleeding tendencies.…”
Section: Overall Hemostasis Potential Assay In Detecting Hypoagulabilmentioning
confidence: 98%
“…Various modifications of the assay were made in later studies. 12,13 Briefly, after addition of thrombin at a lower dose (i.e., 0.04 IU/mL) and platelet reagent as a source of phospholipids, with and without tPA (at 330 ng/mL), to PPP, Abs values are recorded each minute for 40 minutes at a wavelength of 405 nm. Two fibrinaggregation curves are formed and the two AUCs are calculated: that is, the OHP (tPA added) and the overall coagulation potential (OCP; tPA not added) ( Figs.…”
mentioning
confidence: 99%
“…The overall hemostasis potential assay we previously used 8 was modified. Briefly, 50 L of a fibrin formation-triggering cocktail containing rTF, PPL, and CaCl 2 , without or with rt-PA was added to 150 L aliquots of plasma to initiate analyses of the coagulation profile (Cp) and the fibrinolysis profile (Fp), respectively.…”
Section: Overall Hemostasis Potential Analysismentioning
confidence: 99%
“…7 However, the balance between coagulation and fibrinolysis during exercise has not been well defined. This issue may be addressed by measurements of the overall hemostasis potential, 8,9 which measures the balance between thrombininduced fibrin gel formation and plasmin-induced fibrin digestion. Furthermore, as exercise enhances fibrinolysis, it is of considerable interest to investigate how exercise influences the fibrin gel network, being the final outcome of coagulation, using a permeability assay.…”
mentioning
confidence: 99%